A full characterization of all deterministic dominant strategy incentive compatible, ex-post individually rational, and ex-post budget balanced direct mechanisms in the public good provision problem with independent private values - Christoph Kuzmics (Bielefeld University, Center for Mathematical Economics (IMW), 2014)
In this note I give a full characterization of all deterministic direct mechanisms in the public good provision problem with independent private values that are dominant strategy incentive compatible, ex-post individually rational, and ex-post budget balanced.
Keywords: C72; D82; H41; 330; public good provision; asymmetric information; dominant strategy